TREATMENT SETTING AND FOLLOW-UP IN ALCOHOL DEPENDENCE - Prasad, Suveera (Medknow Publications, 2000)
This study aimed at evaluating patient and treatment variables influencing six month treatment outcome in alcohol dependence. 134 serially registered patients selected their treatment setting as either outpatient or inpatient. Sociodemographic variables, alcohol consumption patterns, drinking consequences were measured at intake. Following treatment, drinking patterns and consequences were re-measured at three and six months follow up in each of the groups. 86 of 134 chose the inpatient program and 48 the outpatient program. Overall, 58 maintained total abstinence, and 11 had significantly reduced alcohol consumption at six months follow up. The inpatient group did marginally better than the outpatient group. More severely dependent patients, those with greater physical and psychosocial consequences opted for an inpatient program, and did well. Less severely dependent patients did favourably with outpatient intervention alone. Improvements made within the first three months tended to influence subsequent treatment compliance The observation that less severely dependent individuals who opted for outpatient services did favourably suggests that extensive treatment may be required only for those with more severe dependence or greater psychosocial consequences. Our findings also highlight the need for developing community based low cost interventions.